2015
DOI: 10.1002/cjce.22324
|View full text |Cite
|
Sign up to set email alerts
|

Research on viscoelastic properties of water in waxy crude oil emulsion gels with the effect of droplet size and distribution

Abstract: The viscoelastic properties of gelled oil can reflect its structural characteristics, which are significant for the restart operation of prolonged-shutdown pipelines. The viscoelastic properties of water-in-oil (W/O) emulsions are more complicated on account of the influence from the dispersed water phase, which cannot be ignored. This paper attempts to reveal the relationship of viscoelastic characteristics to temperature and water fraction for waxy crude emulsion gels from a micro perspective. As a basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…When the temperature is further cooled to 28 °C (2.2 °C below the gelation temperature of the waxy crude oil), both the storage modulus and the yield stress turn to increase monotonically with increasing water content, as demonstrated in Figure , which is distinct from the results at their GTs. This monotonic increasing trend of the storage modulus and the yield stress agrees with previous studies, , ,, confirming the enhancement of gel structure by dispersed water droplets when the wax precipitates at the same temperature. However, when the crude oil emulsions just reach their gelation states, the wax-precipitating conditions are different, and the gel structures are composed of different amounts of wax crystals and water droplets.…”
Section: Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When the temperature is further cooled to 28 °C (2.2 °C below the gelation temperature of the waxy crude oil), both the storage modulus and the yield stress turn to increase monotonically with increasing water content, as demonstrated in Figure , which is distinct from the results at their GTs. This monotonic increasing trend of the storage modulus and the yield stress agrees with previous studies, , ,, confirming the enhancement of gel structure by dispersed water droplets when the wax precipitates at the same temperature. However, when the crude oil emulsions just reach their gelation states, the wax-precipitating conditions are different, and the gel structures are composed of different amounts of wax crystals and water droplets.…”
Section: Results and Discussionsupporting
confidence: 91%
“…Existing research has revealed that the GT , or the gel point of a water-in-waxy crude oil emulsion is notably increased with the addition of dispersed water. However, all the present research focuses on the evolution of the rheological properties with different water cut at the same temperature, while the differences of the structural characteristics among different water cut emulsions at their own GTs have not been investigated yet. Besides, the specific reason which causes a crude oil emulsion to gelatinize is also not clear.…”
Section: Introductionmentioning
confidence: 99%
“…During testing, the reference and sample were heated to 60 °C and then cooled to −20 °C at a rate of 5 °C/min. The relationship between heat flow and temperature was recorded to determine the WAT (Figure a). , The measured WATs in these experiment were all above 10 °C, which are higher than the hydrate formation temperature (<7 °C); hence, the solid wax crystals appeared prior to hydrate formation. The details of the measured WATs and the amount of precipitated wax at 3.5 °C are presented in Table S5 of the Supporting Information.…”
Section: Results and Discussionmentioning
confidence: 94%
“…Table gives the compositions of the emulsions so prepared. Emulsion stability was checked by observing the samples at 22 °C (room temperature) for 48 h and after reheating at 50 °C for 2 h. If no macroscopic phase separation was observed during this time period, the emulsions were judged to be stable …”
Section: Methodsmentioning
confidence: 99%
“…Emulsion stability was checked by observing the samples at 22 °C (room temperature) for 48 h and after reheating at 50 °C for 2 h. If no macroscopic phase separation was observed during this time period, the emulsions were judged to be stable. 23 Larger batches of 40% water emulsions for flow loop experiments with the same compositions given in Table 1 were prepared within a reservoir contained within the flow loop itself. Once again, the emulsions were prepared at 50 °C; however, in this case, an overhead mixer was used (RW-20 Digital, IKA, 0−500 rpm) along with three built-in mixing baffles.…”
Section: Methodsmentioning
confidence: 99%